1979
DOI: 10.3168/jds.s0022-0302(79)83204-x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rate in Dairy Cows Inseminated on the Basis of Electronic Probe Measurements

Abstract: A new vaginal probe with two pairs of parallel electrodes 90 degrees apart was designed with a switching arrangement so that electrical resistance (ohms) of the dorsal and the ventral areas of the anterior vagina could be monitored separately during the estrous cycle. Three inseminators probed cows during February--April, 1977, in nine herds in stanchion barn housing. Cows not seen in estrus by 40 to 60 dyas after calving were probed every 3rd day. At each dairyman's option normal cows with a low porbe reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Many studies have indicated that the pH and electrical resistance of the cervical mucus decrease with estrus and are lowest at the time of the LH surge [7, 23,24,25,26,27,28,29,30]. In these previous studies, the measurement probe was maintained or surgically implanted in the mucosa or submucosa of the vagina, and continuous monitoring was carried out in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated that the pH and electrical resistance of the cervical mucus decrease with estrus and are lowest at the time of the LH surge [7, 23,24,25,26,27,28,29,30]. In these previous studies, the measurement probe was maintained or surgically implanted in the mucosa or submucosa of the vagina, and continuous monitoring was carried out in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out on measuring the increase in the activity of cows around estrus by using a pedometer, and this is being used and developed in practice [13,14,15,16,17,18,19,20]. In addition some methods to predict estrus by monitoring internal changes such as body temperature [20,21,22], vaginal mucus pH [23], electrical resistance or conductivity of reproductive tissue and their secretions [7, 21, 24,25,26,27,28,29,30] have been reported. However, neither method has become generally applied.…”
mentioning
confidence: 99%
“…Some studies have reported that lower VER values at the time of insemination are associated with increased probability of conception (Foote et al. 1979; Canfield and Butler 1989; Meena et al.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, changes in vaginal resistance have a closer relationship with the timing of ovulation (Smith and others 1989). The pregnancy rate was higher (52 per cent) in animals inseminated with low vaginal resistance, and not oestrus behaviour than animals with oestrus signs (49 per cent) (Foote and others 1979).…”
Section: Discussionmentioning
confidence: 96%